The Effect of Temperature and Extraction Time on The Physicochemical Properties of Pectin Extracted from Rambutan Peel Waste (Nephelium lappaceum L.): Pengaruh Suhu dan Waktu Ekstraksi Terhadap Karakteristik Fisikokimia Pektin dari Limbah Kulit Rambutan (Nephelium lappaceum L.) - Hellena Istrada; Luqman Agung Wicaksono; Muhammad Alfid Kurnianto; Anugerah Dany Priyanto; Hadi Munarko; Andre Yusuf Trisna Putra (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
Rambutan (Nephelium lappaceum L.) is a tropical fruit commonly grown in Southeast Asia, particularly Indonesia and Malaysia. High consumption of rambutan generates large amounts of peel waste, which remains underutilized despite its potential. Rambutan peel contains approximately 26% pectin and hemicellulose, making it a potential alternative source of pectin to reduce dependence on imports. This study aimed to utilize rambutan peel as an alternative source of pectin. The research investigated the effect of extraction temperature (70, 80, 90 °C) and extraction time (60, 90, 120 min) on the characteristics of pectin using a conventional acid extraction method with a completely randomized design (CRD). Temperature and time variables shows significant effects (P ≤ 0.05) on yield, moisture content, ash content, equivalent weight, methoxyl content, galacturonic acid content, and degree of esterification. Pectin extraction from rambutan peel at 80 °C for 120 min produced the optimal pectin yield (7.34%), meeting both SNI and IPPA standards. Abstrak Rambutan (Nephelium lappaceum L.) adalah buah tropis yang banyak tersebar di Asia Tenggara, utamanya Indonesia dan Malaysia. Tingginyakonsumsi rambutan menimbulkan limbah kulit dalam jumlah besar, namun pemanfaatannya masih belum maksimal. Kulit rambutan mengandung 26% pektin dan hemiselulosa, berpotensi sebagai sumber pektin alternatif untuk mengurangi ketergantungan impor. Tujuan penelitian ini untuk memanfaatkan kulit rambutan sebagai sumber pektin alternatif. Penelitian ini mengkaji pengaruh suhu (70, 80, 90 °C) dan waktu ekstraksi (60, 90, 120 menit) terhadap karakteristik pektin menggunakan metode konvensional dengan ekstraksi asam serta rancangan acak lengkap (RAL). Variable suhu dan waktu menunjukkan pengaruh signifikan (P≤0,05) terhadap rendemen, kadar air, kadar abu, berat ekuivalen, kadar metoksil, kadar asam galakturonat, dan derajat esterifikasi. Ekstraksi pektin kulit rambutan pada suhu 80 °C dan selama 120 menit dapat menghasilkan rendemen pektin yang optimal (7,34%) sesuai dengan SNI dan IPPA.